2015
DOI: 10.1088/1748-9326/10/3/034014
|View full text |Cite
|
Sign up to set email alerts
|

Mapping dynamics of deforestation and forest degradation in tropical forests using radar satellite data

Abstract: Mapping anthropogenic forest disturbances has largely been focused on distinct delineations of events of deforestation using optical satellite images. In the tropics, frequent cloud cover and the challenge of quantifying forest degradation remain problematic. In this study, we detect processes of deforestation, forest degradation and successional dynamics, using long-wavelength radar (L-band from ALOS PALSAR) backscatter. We present a detection algorithm that allows for repeated disturbances on the same land, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 51 publications
1
62
0
1
Order By: Relevance
“…This data set has a higher temporal, but coarser spatial resolution than Landsat, and is also sensitive to aerosols and cloud cover. Other vegetation data sets that can capture vegetation dynamics are for example the observations based on long-wavelength radar backscatter (Joshi et al, 2015), where deforestation, forest degradation and the follow-up vegetation cover could be captured, and those based on observations from the SeaWinds Ku-band scatterometer (Frolking et al, 2012), which have been shown to capture gross forest loss in the Tropics. Also lidar data can be used to estimate forest biomass, and can thus capture vegetation dynamics (Mitchard et al, 2012).…”
Section: J E Van Marle Et Al: Annual South American Forest Lossmentioning
confidence: 99%
“…This data set has a higher temporal, but coarser spatial resolution than Landsat, and is also sensitive to aerosols and cloud cover. Other vegetation data sets that can capture vegetation dynamics are for example the observations based on long-wavelength radar backscatter (Joshi et al, 2015), where deforestation, forest degradation and the follow-up vegetation cover could be captured, and those based on observations from the SeaWinds Ku-band scatterometer (Frolking et al, 2012), which have been shown to capture gross forest loss in the Tropics. Also lidar data can be used to estimate forest biomass, and can thus capture vegetation dynamics (Mitchard et al, 2012).…”
Section: J E Van Marle Et Al: Annual South American Forest Lossmentioning
confidence: 99%
“…Understanding the processes of LUCC is of paramount importance towards more sustainable land management and will aid global initiatives, such as reducing emissions from deforestation and forest degradation (REDD+) [9,10]. However, quantifying LUCC remains a challenge, partly since the dynamics and trajectories of change are complex and fast-evolving [3,11] and partly since robust methods for analyses are still in development for many LUCC processes.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensors operate on a variety of basic physical principles, recording the electromagnetic properties of a land surface (either the energy reflected (optical sensors), emitted (thermal infrared or passive microwave sensors) or scattered (active radar sensors)) and, hence, provide a variety of information on land properties. However, considerable challenges to mapping LUCC using remote sensing data persist; the data are not always uniquely linked to land cover and are ambiguously related to land use, hence commonly requiring the use of heuristic, empirical, e.g., [11,27], or physically-based models [28] to infer land properties. Further, land use information must often be inferred based on integration with ground-knowledge or user interpretation [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…Although a footprint size of 25 m will not enable the high resolution mapping that we are familiar with from small footprint LiDAR, the scientific objectives of the mission include modelling finer scale structure [133]. A combination of Landsat, EnMAP, FLEX, HySPIRI and GEDI LiDAR will combine structural and spectral information and improve the modelling, prediction and understanding of FH [134][135][136][137][138][139]. Examples of the main findings from LiDAR studies in forest analysis are given in Table 6.…”
Section: Light Detection and Ranging (Lidar)mentioning
confidence: 99%
“…Estimation of ST/STV of FH [14,16,138,139] Implementation of multi-sensor RS in modelling approaches improves the discrimination, quantification and accuracy when estimating ST/STV. [197] Multiple platforms for a given sensor type, e.g., the forthcoming Radarsat Constellation of three platforms provides potential for more frequent data acquisition.…”
Section: Application Example Studies Main Findingsmentioning
confidence: 99%